STUDY ON THE SHRINKAGE POROSITY OF AUTOMOTIVE PARTS QUALITY: THE INFLUENCE OF REINFORCED SHELL MOLD THICKNESS IN INVESTMENT CASTING - Khoiruddin, Sukhoiri; Darmadi, Djarot B.; Huang, Cheng-Fu; Lee , Sheng-Chan; Chan, Chien-Wei (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2025)
This study investigates the effect of shell mold thickness on shrinkage porosity observed through numerical simulation using a computer-aided numerical testing (CAE) approach and testing of mechanical, thermal, and physical properties of shell molds. This study investigated whether the thermal properties of different shell mold layer thicknesses. The results showed that the modulus of rupture (MOR) had a value of 6.66 MPa, the permeability was in the range of 1.8x10-¹² m² to 6.6x10-¹² m², the heat transfer coefficient (HTC) had a value in the range of 900 W/m²-K to 660 W/m²-K. The CAE simulation shows that the initial coating thickness will cause problems in the thick corner area for automotive parts. To reduce the hot spot area is to increase the thickness of the mold shell to reduce the percentage of hot spots, which can reduce the possibility of shrinkage formation by 34% that occurs at a mold shell thickness of 6.5 layers can be reduce about 24% compared shell thickness of 4.5 layers. In this study, the best solution to increase the productivity of investment casting is the selection of mold thickness and here for objects that have high dimensions and accuracy must be correct in determining the use of shell mold thickness because different objects will certainly affect the defects that occur.